If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 10 = 64 + -3x Reorder the terms: 10 + 6x = 64 + -3x Solving 10 + 6x = 64 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 10 + 6x + 3x = 64 + -3x + 3x Combine like terms: 6x + 3x = 9x 10 + 9x = 64 + -3x + 3x Combine like terms: -3x + 3x = 0 10 + 9x = 64 + 0 10 + 9x = 64 Add '-10' to each side of the equation. 10 + -10 + 9x = 64 + -10 Combine like terms: 10 + -10 = 0 0 + 9x = 64 + -10 9x = 64 + -10 Combine like terms: 64 + -10 = 54 9x = 54 Divide each side by '9'. x = 6 Simplifying x = 6
| 0=4x^3-12x^2-24x+32 | | .04x^2-4x=0 | | 2[5+2(9-4)]= | | 12+8x=4x+20 | | 9u+4+8t+3u= | | 5-2x+2=15 | | 2y=6-2.5x | | 9xsquared+16x=41 | | 9x+2=-5 | | 3x^2-12x-5=-6x^2 | | 6=2y+2.5x | | 6=2.5x+2y | | -9x+2=5 | | 5=3x-2+4x+1 | | 8x-(22x+7)=5x(2x-2)+8 | | 7x+5y-5(4x-7y)= | | B=(r+k)f | | y=15-10 | | 9y-8y-3=7 | | -81=5x-2(-2x+9) | | 3p^5=12 | | 2x^2-7x-1=3 | | 2(-4+3y)+6y=5 | | 2x+14+12y= | | x+(x*.15)=40 | | (x+7)+9=0 | | 9(z+1)-4(z-4)=2(z-1)+2(z-3) | | -3.3y=-23.1 | | 2x+14+22y= | | 14=18-4c | | -1(w-13)=5 | | sin(x)+1=0 |